Application of Ftir-Atr Spectroscopy in Combination With Multivariate Analysis to Analyse Synthetic Drugs Adulterant in Ternary Mixtures of Herbal Medicine Products - Fatmarahmi, Dharmastuti Cahya; Susidarti, Ratna Asmah; Swasono, Respati Tri; Rohman, Abdul (Indonesian Journal of Pharmacy, 2022)
To against the increasing number of adulteration reports in herbal medicine products in Indonesia, specifically Jamu in powder dosage form, a rapid, efficient, inexpensive method is required. This study was aimed to develop an approach for quantification and classification of an unadulterated herbal medicine product with synthetic drug (prednisone and metamizole) by combining FTIR Spectroscopy and multivariate calibration (PLSR and PCR) as well as discriminant analysis (DA). The spectra data of three individual types of reducing herbal pain products were scanned and collected by FTIR-ATR in the mid-infrared region and further analyzed by two multivariate calibrations to exhibit the optimum mode for quantification analysis of each sample reducing herbal pain product. Based on statistical parameter value, PCR analysis of each model demonstrated the highest value of R2 in both calibration and validation and the lowest value of root mean square of calibration (RMSEC) and root mean square of prediction (RMSEP). The discriminant analysis (DA) was also performed in this study to classify pure reducing pain herbal medicine products without any drugs contaminant and adulterated with synthetic drugs. The outcome of DA was shown by Cooman’s plot and DA could discriminate adulterated and unadulterated reducing pain herbal medicine products with 100% accuracy level. FTIR-ATR spectroscopy in the mid-infrared region coupled with chemometrics could be a potential analytical technique to detect synthetic drugs contaminant in herbal products.